2015
DOI: 10.1016/j.ijdevneu.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Early life trauma is associated with decreased peripheral levels of thyroid‐hormone T3 in adolescents

Abstract: An adverse early life environment can induce changes on behavioral and metabolic responses later in life. Recent studies in rats showed that the quality of maternal care as measured by high levels of pup licking and grooming (LG) was associated with changes in the relationship between the precursor thyroid-hormone T4 and the more active T3. Here we investigated if early exposure to childhood abuse is associated with thyroid-hormone levels in human adolescents. Given the empirical evidence from animal models sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…Accordingly, in the obese population, rates of ELS/CT exposure are reported to be almost twice as high as in the non-obese population (69 vs. 39%) (283). Furthermore, ELS/CT has been repeatedly found to be independently associated with increased overall metabolic risk (284,285), obesity and increased visceral fat deposition (286)(287)(288), decreased HDL, increased LDL levels and lower HDL/LDL ratio (289,290), higher triglyceride levels (285), an overall prediabetic state (e.g., impaired insulin sensitivity) (291), reduced T3 levels and abnormal metabolism of thyroid hormones (292), enhanced risk for emotional eating as a self-regulatory coping strategy (293) and higher prevalence of metabolic syndrome (290,294,295) in later life, while some studies have suggested a dose-dependent relation in these associations (288,296).…”
Section: Metabolismmentioning
confidence: 99%
“…Accordingly, in the obese population, rates of ELS/CT exposure are reported to be almost twice as high as in the non-obese population (69 vs. 39%) (283). Furthermore, ELS/CT has been repeatedly found to be independently associated with increased overall metabolic risk (284,285), obesity and increased visceral fat deposition (286)(287)(288), decreased HDL, increased LDL levels and lower HDL/LDL ratio (289,290), higher triglyceride levels (285), an overall prediabetic state (e.g., impaired insulin sensitivity) (291), reduced T3 levels and abnormal metabolism of thyroid hormones (292), enhanced risk for emotional eating as a self-regulatory coping strategy (293) and higher prevalence of metabolic syndrome (290,294,295) in later life, while some studies have suggested a dose-dependent relation in these associations (288,296).…”
Section: Metabolismmentioning
confidence: 99%
“…Based on the consideration that the onset and course of hypothyroidism is often insidious and may be precipitated by maternal states and conditions that precede pregnancy, we were particularly interested in considering the role of stress exposure from a maternal life course perspective. We selected exposure to childhood maltreatment (CM) as our primary variable of interest for the following reasons: a) CM represents among the most pervasive and pernicious stressors affecting around one third of the general population, with life-long biological, psychological and behavioral consequences (e.g., Heim et al, 2010); b) we and others have previously demonstrated that a woman’s exposure to CM can produce alterations in several features of gestational biology that relate to embryonic/fetal development (Cammack et al, 2011; Mason et al, 2016; Moog et al, 2016; Shea et al, 2007); c) CM exposure has been associated with reduced thyroid activity in the non-pregnant state (Haviland et al, 2006; Machado et al, 2015; Sinai et al, 2014), with thyroid dysfunction in the postpartum period (Plaza et al, 2010; Plaza et al, 2012), and, more generally, with a higher risk of autoimmune disorders (Dube et al, 2009; Goodwin and Stein, 2004); and d) children of women exposed to CM exhibit an increased risk of developing some of the same behavioral disorders that have been observed in children with moderate maternal thyroid dysfunction (Miranda et al, 2013; Rijlaarsdam et al, 2014; Thompson, 2007). In light of these observations, we hypothesized that women exposed to CM may exhibit an increased likelihood of thyroid dysfunction in pregnancy, a time period of particular importance for not only the mother but also for her developing fetus.…”
Section: Introductionmentioning
confidence: 99%
“…За останні роки значно розширилися уявлення про стрес як розгалужену системну реакцію організму, яка, за певних умов, може спричинювати порушення функцій багатьох фізіологічних систем, зокрема, серцево-судинної, нервової; дисфункції ендокринної системи на рівні продукції катехоламінів, гормонів щитоподібної, статевих залоз. Ранні життєві психічні травми у підлітків супроводжуються зниженням рівня трийодтироніну (Machado et al, 2015). Гострий стрес у людей характеризується активацією ліполізу, переважаючими енергосубстратами виступають ліпіди.…”
Section: таблицяunclassified